Hydroxylated polymethoxyflavones reduce the activity of pancreatic lipase, inhibit adipogenesis and enhance lipolysis in 3T3-L1 mouse embryonic fibroblast cells - Bilal, Ahmad; Friar, Emily P.; Muhammad Sufyan, Vohra; Nasar, Khan; Serpell, Christopher J.; Garrett, Michelle D.; Loo, Jason Siau Ee; Fong, Isabel Lim; Eng, Hwa Wong (Elsevier Science Direct, 2023)
Hydroxylated polymethoxyflavones (HPMFs) have been shown to possess various anti-disease effects, including against obesity. This study investigates the anti-obesity effects of HPMFs in further detail, aiming to gain un- derstanding of their mechanism of action in this context. The current study demonstrates that two HPMFs; 3′ - hydroxy-5,7,4′ ,5′-tetramethoxyflavone (3′OH-TetMF) and 4′ -hydroxy-5,7,3′ ,5′ -tetramethoxyflavone (4′OH- TetMF) possess anti-obesity effects. They both significantly reduced pancreatic lipase activity in a competitive manner as demonstrated by molecular docking and kinetic studies. In cell studies, it was revealed that both of the HPMFs suppress differentiation of 3T3-L1 mouse embryonic fibroblast cells during the early stages of adipo- genesis. They also reduced expression of key adipogenic and lipogenic marker genes, namely peroxisome proliferator-activated receptor-gamma (PPARγ), CCAAT/enhancer-binding protein α and β (C/EBP α and β), adipocyte binding protein 2 (aP2), fatty acid synthase (FASN), and sterol regulatory element-binding protein 1 (SREBF 1). They also enhanced the expression of cell cycle genes, i.e., cyclin D1 (CCND1) and C-Myc, and reduced cyclin A2 expression. When further investigated, it was also observed that these HPMFs accelerate lipid breakdown (lipolysis) and enhance lipolytic genes expression. Moreover, they also reduced the secretion of proteins (adipokines), including pro-inflammatory cytokines, from mature adipocytes. Taken together, this study concludes that these HPMFs have anti-obesity effects, which are worthy of further